Algorithm for Designing Professional Retraining Programs Based on a Competency Approach - Rushana R. Anamova; Leonid V. Bykov; Dmitri A. Kozorez (MDPI AG, 2020)
A new methodology is proposed for designing professional retraining programs for aviation, rocket, and space industry employees, focused on the formation of the necessary competencies. The novelty of the proposed method is in the formalization of the design process and the use of digital technologies. The advantage is the use of a modular principle of program design, which provides the opportunity to implement individual training paths for workers in industrial enterprises. The methodology was successfully tested at the Moscow Aviation Institute (National Research University) in the provision of educational services to enterprises in the aviation and aerospace industries.